Self‐Adjusting Metal–Organic Framework for Efficient Capture of Trace Xenon and Krypton. Issue 11 (27th January 2022) - Niu, Zheng; Fan, Ziwen; Pham, Tony; Verma, Gaurav; Forrest, Katherine A.; Space, Brian; Thallapally, Praveen K.; Al‐Enizi, Abdullah M.; Ma, Shengqian
Abstract: The capture of the xenon and krypton from nuclear reprocessing off‐gas is essential to the treatment of radioactive waste. Although various porous materials have been employed to capture Xe and Kr, the development of high‐performance adsorbents capable of trapping Xe/Kr at very low partial pressure as in the nuclear reprocessing off‐gas conditions remains challenging. Herein, we report a self‐adjusting metal‐organic framework based on multiple weak binding interactions to capture trace Xe and Kr from the nuclear reprocessing off‐gas. The self‐adjusting behavior of ATC‐Cu and its mechanism have been visualized by the in‐situ single‐crystal X‐ray diffraction studies and theoretical calculations. The self‐adjusting behavior endows ATC‐Cu unprecedented uptake capacities of 2.65 and 0.52 mmol g −1 for Xe and Kr respectively at 0.1 bar and 298 K, as well as the record Xe capture capability from the nuclear reprocessing off‐gas. Our work not only provides a benchmark Xe adsorbent but proposes a new route to construct smart materials for efficient separations. Abstract : A self‐adjusting metal–organic framework has been proposed for capturing trace Xe and Kr from the nuclear reprocessing off‐gas. The self‐adjusting behavior endows ATC‐Cu the highest Xe and Kr capacity at 0.1 bar and 298 K, as well as a benchmark for capturing low concentration Xe and Kr. The mechanism of the self‐adjusting behavior has been studied through single‐crystal X‐ray diffraction experiments and computational calculations.